Research trends and frontiers on antiphospholipid syndrome: A 10-year bibliometric analysis (2012–2021) - Wu, Teng; Huang, Wei; Qi, Jiaping; Li, Yixuan; Zhang, Yuan; Jiang, Huan; Wang, Jing; Zhang, Ju; Jiang, Zhaoyu; Chen, Lin; Ying, Zhenhua (Frontiers in Pharmacology, 2022)
Objectives: A growing body of studies related to antiphospholipid syndrome (APS) have been published in recent years. Nevertheless, there is a lack of visualized and systematic analysis in the literature on APS. Hence, this study sought to conduct a bibliometric analysis to identify research status and discover frontiers in the field. Methods: Articles and reviews concerning APS were acquired from the Web of Science Core Collection (WoSCC) database. CiteSpace, VOSviewer and a bibliometric online analysis platform were employed to conduct a visualization and knowledge-map analysis. Results: A total of 1,390 publications regarding APS were identified. Globally, Italy contributed the most publications. The University of Padua was the most productive institution. Lupus ranked first in both the most published and most co-cited journals. Savino Sciascia and Spiros Miyakis were the most prolific and most co-cited authors, respectively. “Vitamin K antagonists (VKA)” and “immunoglobulin A (IgA)” were current research foci. Burst analysis of keywords suggested that “neutrophil extracellular trap (NET),” “direct oral anticoagulant (DOAC),” “open label,” “outcome,” “hydroxychloroquine (HCQ),” and “arterial thrombosis (AT)” were significant future research frontiers. Conclusions: The scientific literature on APS has increased steadily in the past 10 years. The clinical studies on the treatment and mechanism research of APS are recognized as promising research hotspots in the domain of APS. The research status and trends of APS publications from the bibliometric perspective can provide a practical guide and important reference for subsequent studies by researchers and physicians in the domain.